2019
DOI: 10.3389/fmicb.2019.00728
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance, Virulence Determinants, and Biofilm Formation of Enterococcus Species From Ready-to-Eat Seafood

Abstract: Enterococcus species form an important population of commensal bacteria and have been reported to possess numerous virulence factors considered significantly important in exacerbating diseases caused by them. The present study was designed to characterize antibiotic-resistant and virulent enterococci from ready-to-eat (RTE) seafood. A total of 720 RTE shrimp samples comprising sauced shrimp ( n = 288), boiled shrimp ( n = 216), and smoked shrimp ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
59
4
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(82 citation statements)
references
References 97 publications
(129 reference statements)
18
59
4
1
Order By: Relevance
“…Other studies have shown that E. faecalis and E. faecium constitute the dominant flora in isolates obtained from animal‐originated foods (Cho et al, 2013; Jiménez et al, 2013; Morandi et al, 2015; Valenzuela, Benomar, Abriouel, Cañamero, & Gálvez, 2010; Yogurtcu & Tuncer, 2013). In contrast to our results, vancomycin‐resistant E. faecalis and/or E. faecium strains were isolated from animal‐originated foods in Slovakia (Kročko et al, 2011), Korea (Cho et al, 2013), Turkey (Çetinkaya et al, 2013), Spain (Guerrero‐Ramos et al, 2016), and Nigeria (Igbinosa & Beshiru, 2019). Pediococcus and Weissella can be isolated from animal‐originated foods as well as the commonly‐isolated Enterococcus species.…”
Section: Resultscontrasting
confidence: 99%
“…Other studies have shown that E. faecalis and E. faecium constitute the dominant flora in isolates obtained from animal‐originated foods (Cho et al, 2013; Jiménez et al, 2013; Morandi et al, 2015; Valenzuela, Benomar, Abriouel, Cañamero, & Gálvez, 2010; Yogurtcu & Tuncer, 2013). In contrast to our results, vancomycin‐resistant E. faecalis and/or E. faecium strains were isolated from animal‐originated foods in Slovakia (Kročko et al, 2011), Korea (Cho et al, 2013), Turkey (Çetinkaya et al, 2013), Spain (Guerrero‐Ramos et al, 2016), and Nigeria (Igbinosa & Beshiru, 2019). Pediococcus and Weissella can be isolated from animal‐originated foods as well as the commonly‐isolated Enterococcus species.…”
Section: Resultscontrasting
confidence: 99%
“…A similar finding could be seen among enterococcal isolates from animal and food sources [13,35,36]. Although resistance mechanisms for tetracycline and erythromycin were well understood and present among most of the enterococcal isolates across all species, AR genes could not be identified for many other antimicrobial drugs [13,35,36]. The genetic mechanisms of AR in non-faecalis and non-faecium enterococcal species seem to be quite different from those of E. faecalis and E. faecium, and the understanding of AR mechanisms needs to be improved for different species.…”
Section: Discussionsupporting
confidence: 80%
“…This could indicate that the genetic mechanism for tetracycline resistance is well understood, but not for other drug resistances. A similar finding could be seen among enterococcal isolates from animal and food sources [13,35,36]. Although resistance mechanisms for tetracycline and erythromycin were well understood and present among most of the enterococcal isolates across all species, AR genes could not be identified for many other antimicrobial drugs [13,35,36].…”
Section: Discussionsupporting
confidence: 58%
“…As enterococci potentially transfer resistant genes from enteric bacteria in animals to humans via the food chain and they are potential pathogens, they have become a global public health concern. In previous reports, available data showed MDR Enterococcus with a variety of virulent determinants isolated from commensal animals, such as chickens, pigs and cattle (Diarra et al, 2010;Beshiru et al, 2017;De Jong et al, 2019;Igbinosa and Beshiru, 2019). However, there has been no available data on enterococci isolated from yaks.…”
Section: Introductionmentioning
confidence: 99%